PARLOMA – A Novel Human-Robot Interaction System for Deaf-Blind Remote Communication. (15th May 2015) - Russo, Ludovico Orlando; Farulla, Giuseppe Airò; Pianu, Daniele; Salgarella, Alice Rita; Controzzi, Marco; Cipriani, Christian; Oddo, Calogero Maria; Geraci, Carlo; Rosa, Stefano; Indaco, Marco
Deaf-blindness forces people to live in isolation. At present, there is no existing technological solution enabling two (or many) deaf-blind people to communicate remotely among themselves in tactile Sign Language (t-SL). When resorting to t-SL, deaf-blind people can communicate only with people physically present in the same place, because they are required to reciprocally explore their hands to exchange messages. We present a preliminary version of PARLOMA, a novel system to enable remote communication between deaf-blind persons. It is composed of a low-cost depth sensor as the only input device, paired with a robotic hand as the output device. Essentially, any user can perform hand-shapes in front of the depth sensor. The system is able to recognize a set of hand-shapes that are sent over the web and reproduced by an anthropomorphic robotic hand. PARLOMA can work as a "telephone" for deaf-blind people. Hence, it will dramatically improve the quality of life of deaf-blind persons. PARLOMA has been presented and supported by the main Italian deaf-blind association, Lega del Filo d'Oro. End users are involved in the design phase.